2019
DOI: 10.4196/kjpp.2019.23.6.427
|View full text |Cite
|
Sign up to set email alerts
|

Role of nociceptin/orphanin FQ and nociceptin opioid peptide receptor in depression and antidepressant effects of nociceptin opioid peptide receptor antagonists

Abstract: Nociceptin/orphanin FQ (N/OFQ) and its receptor, nociceptin opioid peptide (NOP) receptor, are localized in brain areas implicated in depression including the amygdala, bed nucleus of the stria terminalis, habenula, and monoaminergic nuclei in the brain stem. N/OFQ inhibits neuronal excitability of monoaminergic neurons and monoamine release from their terminals by activation of G protein-coupled inwardly rectifying K+ channels and inhibition of voltage sensitive calcium channels, respectively. Therefore, NOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 170 publications
(295 reference statements)
0
6
0
1
Order By: Relevance
“…Unlike µ- and δ-opioid receptor subtypes, activation of ĸ-opioid and nociceptin opioid peptide (NOP) receptors are generally associated with a decrease in central monoaminergic activity (Gavioli and Calo, 2013; Schlicker and Morari, 2000; Tao and Auerbach, 2005; Yılmaz et al, 2006). It has also been suggested that agonists of ĸ- or NOP-receptors cause negative effects on mood (Ji et al, 2021; Toll et al, 2021), and blocking these receptors causes antidepressant-like effects (Jacobson et al, 2020; Park et al, 2019; Shang et al, 2021). Therefore, further studies are needed to clarify whether the antidepressant-like activity of tofisopam is associated with any attenuation in the functions of ĸ- and NOP-opioidergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike µ- and δ-opioid receptor subtypes, activation of ĸ-opioid and nociceptin opioid peptide (NOP) receptors are generally associated with a decrease in central monoaminergic activity (Gavioli and Calo, 2013; Schlicker and Morari, 2000; Tao and Auerbach, 2005; Yılmaz et al, 2006). It has also been suggested that agonists of ĸ- or NOP-receptors cause negative effects on mood (Ji et al, 2021; Toll et al, 2021), and blocking these receptors causes antidepressant-like effects (Jacobson et al, 2020; Park et al, 2019; Shang et al, 2021). Therefore, further studies are needed to clarify whether the antidepressant-like activity of tofisopam is associated with any attenuation in the functions of ĸ- and NOP-opioidergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be remarked that the expression of NOP receptors in different neuronal ensembles within the same brain regions could lead to the disinhibition of their outputs in response to N/OFQ. Furthermore, given the adaptability of the N/OFQ-NOP receptor system in response to behaviorally relevant experiences, the net effects of its activation/inactivation could also be regulated by state-dependent physiological and pathological factors such as anxiety, mood disorders and drug addiction (for review see [ 57 , 59 ]. Consistently, neuroanatomical data demonstrated a high expression of N/OFQ and NOP receptor in brain regions of the mesocorticolimbic system, the extended amygdala and the hypothalamus, that are known to subserve the regulation of motivated behaviors, stress response and affection [ 17 , 18 , 60 , 61 , 62 ].…”
Section: Neurobiology Of the N/ofq-nop Receptor Systemmentioning
confidence: 99%
“…This effect was specific to the BNST, since intra-CeA N/OFQ microinjections were ineffective [ 127 ]. Although highly speculative, an intriguing explanation is that N/OFQ could promote stress response by silencing the inhibitory signals that the BNST tonically sends to the PVN [ 59 ]. N/OFQ and NOP receptors mRNAs are also enriched in the suprachiasmatic nucleus of the hypothalamus (SCN) [ 128 , 129 ].…”
Section: Neurobiology Of the N/ofq-nop Receptor Systemmentioning
confidence: 99%
“…KNT-127 [121], Rubiscolin-6 [122], and SNC80 [123] are preclinical DOR receptor agonists that decreased depressive-like behaviors in mouse models of depression. N/OFQ is an endogenous opioid peptide that binds to nociceptin receptor (NOPr), part of the opioid receptor family [124]. NOPr antagonists such as LY2940094 [125] and UFP-101 [126] reduced anhedonia and rescued stress-like and anxiety-like behaviors by restoring neurogenesis after chronic stress.…”
Section: Opioid Receptorsmentioning
confidence: 99%